2014
DOI: 10.5937/metmateng1402131d
|View full text |Cite
|
Sign up to set email alerts
|

The influence of the chemical composition and type of alloy on corrosion performances of some medium strength Al-Mg-Si series of alloys

Abstract: The effect of the chemical composition, i.e. content of silicone (Si) and other alloying elements (Zr, Mn, etc) on the corrosion behaviour and mechanical properties of Al-Mg-Si (6xxx) type alloys was investigated in this paper. Open circuit corrosion potential (OCP) measurements, linear polarization and potentiodynamic anodic/cathodic polarization were employed in order to determine the corrosion behaviour of artificially aged Al-Mg-Si samples in the chloride ions containing aqueous corrosion solutions. The di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Differences in OCPs of these alloys, in relation to Al99.7, were between 1-4 %. The exceptions were found for the AlMg0.65Si0.76Zr0.1 alloy in chloride solution where the difference is 14 % (about 100 mV) and for the AlMg4Zn1.3Mn0.4 sample immersed in natural water (about 9%, or 60mV) [24]. Figure 3 shows polarization curves of investigated alloys under potentiodynamic scanning conditions in synthetic seawater.…”
Section: Resultsmentioning
confidence: 98%
“…Differences in OCPs of these alloys, in relation to Al99.7, were between 1-4 %. The exceptions were found for the AlMg0.65Si0.76Zr0.1 alloy in chloride solution where the difference is 14 % (about 100 mV) and for the AlMg4Zn1.3Mn0.4 sample immersed in natural water (about 9%, or 60mV) [24]. Figure 3 shows polarization curves of investigated alloys under potentiodynamic scanning conditions in synthetic seawater.…”
Section: Resultsmentioning
confidence: 98%
“…The activity of the ions increases obviously with the decrease in the bounding force of the atoms. Alloying elements also have an effect on the diffusion behavior of the atoms in matrix [17,24]. The migration speed of Li ions is very high because of their high chemical activity and the higher the diffusion coefficient in liquid Al-Li alloys [25].…”
Section: Influence Mechanism Of Lithium On Diffusion Reaction Layermentioning
confidence: 99%
“…Therefore, it is of great theoretical and practical value to study the corrosion behavior of titanium alloy in aluminum-lithium alloy melt. So far, many researchers [15][16][17] have shown that the chemical composition of aluminum alloy melt has a great influence on its corrosion ability. However, there is a lack of research work about the effect of lithium on the dissolution of titanium in aluminum alloy melt, and the evolution and growth law of the diffusion reaction layer (DRL) at the solid-liquid interface.…”
Section: Introductionmentioning
confidence: 99%
“…Aluminum alloys are widely used in aerospace due to their low density, high cost-effectiveness, and excellent thermal/electrical conductivity [ 1 , 2 ]. However, the processing of aluminum alloys requires a high cutting force and heat dissipation, given their high viscosity and severe plastic deformations, and results in a degraded accuracy and surface quality of the processed surfaces [ 3 , 4 ]. In ultrasonic-assisted milling, high-frequency ultrasonic vibrations are applied to process tools or components after the amplitude amplification by the ultrasonic horn, while residual materials are readily removed by ultrasonic waves due to their high and concentrated energy and high impacts [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%